Creating a Brand on the Identity of a Sports Club: Preliminary Report Creating a Brand on the Identity of a Sports Club - Nenad Bulovic; Neven Seric (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2021)
Creating a sports club brand is an important strategic marketing activity. The quality of the content of a sports club brand can be communicated effectively by promoting its key features. A sports club's identity is a critical marketing feature that significantly contributes to differentiation on the market. The paper aims to argue the importance and the marketing practice in Croatian sport of implementing a sports club's identity in its brand image. The research has been conducted during year of 2019 using qualitative and quantitative methods through different sport case studies of three famous basketball and two famous football clubs from Croatia. Although communication of the brand image through its identity is increasingly encouraged in recent scientific literature, it is not yet a common practice in sports in Croatia. Results shows there are no clear links between the brand image and the identity even in Croatian famous professional sport clubs. The sports club's identity is recognized in terms of its existence, social significance, activities, and development to date. The sports brand identity should com- municate the core values of the sports club identity. A distinct brand of a sports club is imperative for desirable positioning in the wider environment. The identity of a sports club is a valuable marketing and strategic element of its brand. The distinctiveness of a sports club brand significantly depends on the implementation of its identity in its image. In sport marketing practice in Croatia it needs to be change.